If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(9 + 2h) = 19 (9 * -4 + 2h * -4) = 19 (-36 + -8h) = 19 Solving -36 + -8h = 19 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -8h = 19 + 36 Combine like terms: -36 + 36 = 0 0 + -8h = 19 + 36 -8h = 19 + 36 Combine like terms: 19 + 36 = 55 -8h = 55 Divide each side by '-8'. h = -6.875 Simplifying h = -6.875
| 19x=85 | | n/14=20 | | -3(u-2)= | | 34-5x+2(X-2)-6=12 | | 18/y=3 | | 4m^2-8m= | | y=3+-3(-1) | | y=3-3(1) | | 8x+5=16x+10 | | 5x+7y=164 | | 3a^2+12a-4=0 | | 0.40x+0.30(70)=0.20(69) | | -6x^3=0 | | 5x-20y= | | B-9=16 | | 5/8n=-10 | | F/193.75=15 | | x+x(0.13)=4000 | | v^2-9v-2=0 | | 1/9d=3 | | 7x(x+3)+5=3x(x+2) | | k/9=1/3 | | 4z+9=11 | | 80/4-8=12 | | 3/5a=2 | | Z+5a=55 | | 3y^3-6y^2-8y+32=0 | | x^.25/x^.857 | | x=(0.72/0.4)-1.4 | | log(10)1024=y | | 9+L=89 | | z^2+2z+i=0 |